Автоматизированное проектирование учебное пособие - Сикора, Е. А. специалист в области машиностроения доцент кафедры автоматизации и роботизации в машиностроении Томского политехнического университета 1984- (Изд-во ТПУ, 2012)
Fundamentals of CAD, hardware in computer-aided design, computer graphics software, choice of means, development cycles and formation of specialized databases are considered and discussed. Some features of the most common methods and devices are also shown.